Draft Annual Plan 1980-81 Part-II-Plan Proposals in Detail - Government of Goa, Daman and Diu (Government of Goa, Daman and Diu, 1979)
The Draft Annual Plan 1980–81 of the Government of the Union Territory of Goa, Daman and Diu outlines comprehensive sectoral development proposals with a primary focus on Agriculture and Allied Services as a foundation for economic growth and rural prosperity. Major agricultural initiatives include seed multiplication and distribution, expansion of High Yielding Varieties of paddy and other crops, sugarcane development, and strengthening of government farms at Kalay, Margao, Mapusa, Chimbel, and Daman to support quality seed production and horticultural planting material. The plan emphasizes increased crop productivity through demonstrations, improved package practices, pest control measures, pulse intensification, and multiple cropping strategies. Complementary sectors such as minor irrigation, soil and water conservation, animal husbandry, dairying, fisheries, and forestry are integrated to enhance resource utilization and farmer incomes. Institutional support is strengthened through agricultural credit, marketing, cooperative development, and command area development. Infrastructure expansion in water and power, transport and communication, and industrial development is also proposed to sustain overall growth. Social and community services including education, technical education, medical and public health, housing, urban development, labour welfare, nutrition, and social welfare receive significant attention to improve quality of life. The plan further reinforces economic services, statistical systems, planning machinery, and administrative capacity to ensure effective implementation, reflecting a coordinated and multi-sectoral approach to balanced regional development.
Department of Planning & Statistics Panaji - Goa November - 1979
Department of Planning & Statistics Panaji - Goa November - 1979
Keywords: Agriculture Production; Seed Multiplication; High Yielding Varieties Programme; Sugarcane Development Programme; Minor Irrigation; Soil and Water Conservation; Animal Husbandry; Fisheries Development; Rural Credit; Panchayati Raj; Technical Education; Public Health Services